On Blood And Fire: A Retelling Of Algeria’s Black Decade In Yasmina Khadra’s Les Agneaux Du Seigneur - Ziane, Fouzia; Baghdadi, Assia; mehdi, rachid (Journal of Social Sciences and Humanities, 2021)
Many literary works have revolted to study the apocalyptic reality of 1990s Algeria in its fight against terrorism. Among the pens which rose to write and describe the violence the Algerians were living in: that of Yasmina Khadra. This writer, but also an ex-officer in the Algerian military body, through his novel Les agneaux du Seigneur tempts to unveil a state of decomposition and desolation of a society prey to the civil war. The core aim of this article is to examine how Les agneaux du Seigneur portrays, explores, and analyzes the Algerian Civil War. Indeed, the article analyzes and interprets the novel through a profound historical and literary contextualization. Algeria’s disorder, its sluggish state, the Islamist movement (The Islamic Salvation Front- FIS), the insurgency, and the dreadful bloody violence that continued throughout the 1990s are crucial thematic elements used to understanding the civil war.